SISTEM INFORMASI DESA TEBARA (KAMPUNG SITUS PRAIJING) BERBASIS WEB - Pandang, Marianti; Umbu Janga , Adelbertus; Fransiska Ledi , Dian (Universitas Medan Area, 2024)
Tebara Village is one of 13 villages located in the administrative area of Waikabubak city sub-district, West Sumba Regency. Tebara Village is the only village in East Nusa Tenggara that is included in the 75 best tourist villages in the 2023 ADWI (Indonesian Tourism Village Award). This website was built using the System Development Life Cycle (SDLC) method with the waterfall model, PHP programming language, Laravel framework, and MySQL database as well as program testing using black-box testing. The results of this research succeeded in designing a village website as an information system through the product design design stage which included identifying functional and non-functional needs, model design, input and output design, and database design. The construction of the Village website as an information system for the Tebara Village Office can help facilitate and expand the dissemination of information carried out by the village government. This also allows access to this information by the public, especially the people of Tebara village. The existence of the Tebara Village website can make it easier for the public to access information related to the village. Users only need to see the information on the website without needing to come directly to the Tebara village office.